Thinking Against Burnout? An Individual’s Tendency to Engage in and Enjoy Thinking as a Potential Resilience Factor of Burnout Symptoms and Burnout-Related Impairment in Executive Functioning - Fleischhauer, Monika; Miller, Robert; Wekenborg, Magdalena Katharina; Penz, Marlene; Kirschbaum, Clemens; Enge, Sören (Frontiers in Psychology, 2019)
The personality trait need for cognition (NFC) refers to individual differences in the tendency to engage in and enjoy cognitive endeavours. In today's working world, which is characterized by increasing cognitive demands, NFC may contribute to resilience against work-related stress and burnout symptoms. We investigated this question in a large population-wide sample of 4,134 individuals (Study 1) and in a sample of 125 students (Study 2). NFC was consistently negatively related to the burnout facets emotional exhaustion and reduced personal efficiency of the Maslach burnout inventory and explained up to 10 % additional variance in burnout symptoms over and above the Five-factor model of personality. In the student sample, where stress factors are mainly cognitive in nature, NFC was the most relevant predictor. In this sample, we additionally investigated whether NFC might be a relevant moderator of the inconsistently found associations between burnout and impairments in cognitive functioning. The participants conducted three cognitive tasks (number-letter-task, 2back-task, and Go/NoGo task) that measure the executive functions switching, updating, and response inhibition, respectively. While burnout was slightly negatively related to working memory performance, NFC did not moderate the relationship between burnout and executive control which could be traced back to the young and healthy sample used to examine this research question. All in all, our results clearly suggests that NFC may be an important individual difference factor contributing to the resilience against burnout, especially if stress factors are cognitive in nature.